Florida Nursery Crops and Landscaping Industry Economic Impacts, Situation, and Outlook - Hayk Khachatryan; Alan W. Hodges (EDIS)
Florida is one of the leading environmental horticulture producers in the United States, ranked second only to California. In 2010, total industry sales were estimated at $12.33 billion. This 10-page report summarizes the current situation, economic impacts, and outlook for the environmental horticulture industry in Florida. Written by Hayk Khachatryan and Alan W. Hodges, and published by the UF Department of Food and Resource Economics, September 2014.